2014
DOI: 10.1021/ol502197p
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidative Homocoupling of Aryl Amines Using Heterogeneous Rhodium Catalysts

Abstract: The first heterogeneous catalyzed oxidative coupling of aryl amines is reported. Aryl amines were dimerized at room temperature under air using a heterogeneous Rh/C catalyst in the presence of acids. By choosing a suitable acidic solvent, biaryl compounds and carbazoles were selectively prepared in good yields. This reaction is operationally simple and provides an efficient synthetic methodology for the preparation of biaryl diamines via oxidative C-H activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 64 publications
1
19
0
1
Order By: Relevance
“…Scheme 4d epicts ac atalytic approach for the oxidative homocoupling of anilines. [29] In this case,asystem comprised of rhodium adsorbed on carbon, air,a nd TFAa sasolvent showed the highest efficiency.Biaryl amines 20-26 (including p-expanded analogues 20 a-d)w ere obtained selectively in high to excellent yields (up to 99 %). Interestingly,w hen HFIP was used as as olvent, the authors obtained the carbazole-based compound 21 as the sole product in 70 % yield.…”
Section: Oxidative Homocoupling Of Arenes and Heteroarenesmentioning
confidence: 82%
See 1 more Smart Citation
“…Scheme 4d epicts ac atalytic approach for the oxidative homocoupling of anilines. [29] In this case,asystem comprised of rhodium adsorbed on carbon, air,a nd TFAa sasolvent showed the highest efficiency.Biaryl amines 20-26 (including p-expanded analogues 20 a-d)w ere obtained selectively in high to excellent yields (up to 99 %). Interestingly,w hen HFIP was used as as olvent, the authors obtained the carbazole-based compound 21 as the sole product in 70 % yield.…”
Section: Oxidative Homocoupling Of Arenes and Heteroarenesmentioning
confidence: 82%
“…Scheme depicts a catalytic approach for the oxidative homocoupling of anilines . In this case, a system comprised of rhodium adsorbed on carbon, air, and TFA as a solvent showed the highest efficiency.…”
Section: Intermolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
“…Recently, we found that rhodium on carbon functions as an excellent catalyst for the oxidative homocoupling of the aryl amine 1 under mild reaction conditions to provide the dehydrodimer 2 in a high yield (Scheme ) . Notably, this reaction can be carried out with low catalyst loading using air as a terminal oxidant, which is especially advantageous because previous methods usually require a stoichiometric amount of metal salts or oxidants .…”
Section: Methodsmentioning
confidence: 99%
“…[12] Notably,t his reaction can be carried out with low catalyst loading using air as at erminal oxidant, which is especially advantageous because previous methods usually require as toichiometric amount of metal salts or oxidants. [12] Notably,t his reaction can be carried out with low catalyst loading using air as at erminal oxidant, which is especially advantageous because previous methods usually require as toichiometric amount of metal salts or oxidants.…”
mentioning
confidence: 99%
“…Recently,w ef ound that rhodium on carbon functions as an excellent catalyst for the oxidative homocoupling of the aryl amine 1 under mild reaction conditions to provide the dehydrodimer 2 in ah igh yield (Scheme 2). [12] Notably,t his reaction can be carried out with low catalyst loading using air as at erminal oxidant, which is especially advantageous because previous methods usually require as toichiometric amount of metal salts or oxidants. [13] Thus,w ee nvisioned extending the homocoupling to ah eterogeneously catalyzed CDC reaction.…”
mentioning
confidence: 99%